(untitled) (The Spectrum, 2025)
This paper examines Jonas’s journey from sameness to elsewhere as a journey from innocence to experience in Lois Lowry’s novel The Giver. After receiving memories, Jonas does not want to stay in ‘sameness’, going ‘elsewhere.’ This movement is beyond societal expectations. Why does he undertake this arduous and challenging journey? Why must he embark on a journey that leads him towards pain, suffering, imperfection, and ills? Is he happy to be in ‘Elsewhere’ where he experiences unfamiliarity and uncertainty? The study hypothesizes that his journey from sameness to elsewhere is a critique of the seemingly perfect world that the community of Elders has created. Drawing on Sarland’s take on the impossibility of innocence in children, Hunt’s focus on ideological perception in children’s literature, and Nodelman’s explanation on the experience and ideology in the disguise of innocence, the study argues that Jonas’s journey from ‘sameness’ to ‘elsewhere’ is a journey to multiple experiences, knowledge, and wisdom, unlike the sameness where he knows nothing except storing the memories. It concludes that since children constantly move between the world of innocence and experience—‘transitional innocence/experience’, they gain knowledge, new insights, and wisdom by going beyond the expectation of social order created by the community of Elders.